Some estimates of the normal approximation for mixture of Poisson and gamma random variables - Sunklodas, Jonas Kazys (Lietuvos matematikos rinkinys, 2010)
In the paper, we present the upper bound of Lp norms ∆p of the order (a1 + a2)/(DZ)-1/2 for all 1 0, and the random variable Y by the standard gamma distribution Γ (α, 0, 1) with the parameter α > 0.
Keywords: normal approximation; Lp norms; Poisson distribution; gamma distribution; mixture of Poisson and gamma r.v.